Developmental Model of Islamic Microfinance Institution in Minangkabau Muslim Community using Analytical Network Process (ANP) - Awaluddin Awaluddin; Asyari Asyari; Amiur Nuruddin; Saparuddin Siregar (Islam Realitas: Journal of Islamic and Social Studies, 2021)
Abstract This research aims to uncover and map the problems faced by Islamic microfinance institutions (BPRS) both in terms of social and management. Afterward itrevealed, the solutions, strategies, and priority rankings of long-term alternative strategies were revealed using the analytic network process (ANP) method. The methodology used in this study is qualitative which aims to capture the views of sharia experts and scholars on the development of sharia microfinance institutions. The research findings related to the development model of Islamic microfinance institutions are (1). Criteria for the development of Islamic microfinance institutions include management issues,competition issues, policy issues and risk issues. Management problems are the dominant problems found in Islamic Microfinance Institutions with a value 0.427.Then followed by regulatory issues and 0.293 risks and finally 0.278 competition issues, the appraiser's agreement was 0.456 or 45.6%. (2).Then the determination of strategic planning with a value of 0.382 and affirmation of the value of the company and local genius 0.230,rater agreement 0.382 or 38.2%. These results show that the direct involvement of the Muslim community in West Sumatra as shareholders, founders and administrators has not been able to improve the quality of human resources in Islamic microfinance institutions.Penelitian ini bertujuan untuk mengungkap dan memetakan permasalahan yang dihadapi oleh lembaga keuangan mikro syariah (BPRS) baik dari sisi sosial maupun manajemen. Setelah itu, terungkap solusi, strategi, dan peringkat prioritas strategi alternatif jangka panjang dengan menggunakan metode analytic network process (ANP). Metodologi yang digunakan dalam penelitian ini adalah kualitatif yang bertujuan untuk menjaring pandangan para ahli dan cendekiawan syariah tentang perkembangan lembaga keuangan mikro syariah (BPRS). Instrumen analisis yang digunakan adalah Analytical Network Process (ANP) yang digunakan untuk menemukan permasalahan dan prioritas solusi dalam penelitian ini. Temuan penelitian terkait model pengembangan lembaga keuangan mikro syariah adalah (1). Kriteria isu pengembangan lembaga keuangan mikro syariah meliputi isu manajemen, isu persaingan, isu kebijakan dan isu risiko. Masalah manajemen merupakan masalah yang dominan ditemukan pada Lembaga Keuangan Mikro Syariah dengan nilai 0,427. Kemudian disusul masalah regulasi dan risiko 0,293 dan terakhir masalah persaingan 0,278, kesepakatan penilai 0,456 atau 45,6%. (2). Kemudian penetapan strategic planning dengan nilai 0,382 dan penegasan nilai perusahaan dan local genius 0,230, rater agreement 0,382 atau 38,2%. Hasil ini menunjukkan keterlibatan langsung masyarakat muslim Sumbar sebagai pemegang saham,pendiri dan pengurus masih belum mampu meningkatkan kualitas sumber daya manusia di lembaga keuangan mikro syariah.